Women's Advocacy for Appointing Women Qāḍī in Sri Lanka: A Juristic Analysis - M.B. Fowzul (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
The women's organisations in Sri Lanka have been advocating for three decades for appointing women Qāḍī. However, the association of predominant religious leaders, namely All Ceylon Jam-e-athul Ulama (ACJU), opposes women's demands. Consequently, there has been a deadlock between the ACJU and its reform proponents. This deadlock has created chaos and public debate among not only Muslims but among the other religious groups in Sri Lanka. Therefore, to fulfil this timely need, this study analysed the possibilities of the appointment of women Qāḍī (judges) in Sri Lanka from a juristic perspective. Because it is a juristic analysis, this study mainly focuses on secondary data drawn from the Quran and the Hadith and the opinions of classical and modern jurists. However, the interviews were conducted to find the insights of the experts in the Muslim Marriage and Divorce Act (MMDA) of Sri Lanka as primary data, which greatly supported the secondary data. This study deeply delves into the justifications of reform proponents and the counterarguments of religious leaders from a juristic perspective. Finally, this study found that even though the reform proponents propose alternative views to achieve their demand, the ACJU vehemently denies it, criticising that their demand is impracticable, according to the text and the context, since the Shafie Madhhab governs the Muslim Family Law in Sri Lanka. However, this study provides some suggestions and recommendations to curb the malpractices women face in the system.